Formation of phenylacetylene and benzocyclobutadiene in the ortho-benzyne + acetylene reaction. Issue 3 (6th January 2022) - McCabe, Morgan N.; Hemberger, Patrick; Campisi, Dario; Broxterman, Jeger C.; Reusch, Engelbert; Bodi, Andras; Bouwman, Jordy
Abstract : A combined experimental and theoretical study of the ortho -benzyne + acetylene reaction using iPEPICO spectroscopy concludes that phenylacetylene and benzocyclobutadiene are formed in a 2 : 1 ratio under nonequilibrium conditions. Abstract : Ortho -benzyne is a potentially important precursor for polycyclic aromatic hydrocarbon formation, but much is still unknown about its chemistry. In this work, we report on a combined experimental and theoretical study of the o -benzyne + acetylene reaction and employ double imaging threshold photoelectron photoion coincidence spectroscopy to investigate the reaction products with isomer specificity. Based on photoion mass-selected threshold photoelectron spectra, Franck–Condon simulations, and ionization cross section calculations, we conclude that phenylacetylene and benzocyclobutadiene (PA : BCBdiene ) are formed at a non-equilibrium ratio of 2 : 1, respectively, in a pyrolysis microreactor at a temperature of 1050 K and a pressure of ∼20 mbar. The C8 H6 potential energy surface (PES) is explored to rationalize the formation of the reaction products. Previously unidentified pathways have been found by considering the open-shell singlet (OSS) character of various C8 H6 reactive intermediates. Based on the PES data, a kinetic model is constructed to estimate equilibrium abundances of the two products. New insights into the reaction mechanism – with a focus on the OSS intermediates – and the products formed in the o -benzyne + acetylene reaction provide a greater level of understanding of the o -benzyne reactivity during the formation of aromatic hydrocarbons in combustion environments as well as in outflows of carbon-rich stars.